(untitled) - NUR SHADRINA, FARISAH (Language Horizon: Journal of Language Studies, 2014)
Philia Love in C.S Lewis’ Narnia: The Lion, The Witch and The Wardrobe Farisah Nur Shadrina English Literature Faculty of Languages and Arts State University of Surabaya farisah.n@gmail.com Drs. Much Khoiri, M.Si English Department Faculty of Languages and Arts State University of Surabaya much_choiri@yahoo.com Abstrak Tidaklah mudah untuk mendefinisikan apa itu cinta. Bagaimanapun juga, cinta telah menjadi tema umum yang digunakan dalam lagu-lagu, film-film, karya-karya sastra dan kehidupan sehari-hari. Cinta adalah komponen yang penting dalam kehidupan individual dan tampaknya seseorang tidak mungkin dapat hidup tanpa cinta. Cinta tidak hanya menggambarkan sesuatu yang erotis namun juga dapat menggambarkan hubungan antar teman, yang dapat disebut sebagai cinta filia atau persahabatan. Cinta filia atau persahabatan adalah satu tema yang paling banyak digunakan dalam karya sastra anak – anak. Skripsi ini merumuskan dua masalah; bagaimana cinta philia digambarkan oleh karakter-karakter dalam karya sastra anak – anak populer, Narnia: The Lion, The Witch and The Wardrobe karya C.S Lewis dan apa alasan – alasan dan dampak – dampak dari penggunaan cinta filia di dalam novel tersebut. Skripsi ini fokus mendiskusikan cinta filia melalui karakter – karakter (Anak-anak Pevensie dan penduduk Narnia) di dalam novel Narnia: The Lion, The Witch and The Wardrobe karya C.S Lewis dan alasan – alasan mereka serta dampak – dampaknya dalam penggunaan cinta filia. Riset pustaka dengan membaca secara intensif diaplikasikan di dalam skripsi ini sebagai pendekatan untuk analisa data. Untuk menjawab masalah pertama, skripsi ini menggunakan teori cinta oleh Fromm, element – element cinta filia atau persahabatan oleh Moore dan Lewis yang dibantu oleh konsep dari Aristotle and beberapa peneliti lainnya di bidang persahabatan. Masalah kedua dijawab dengan menggunakan konsep motif dalam membangun persahabatan oleh Aristotle yang dibantu oleh penjelasan Lewis dan Fromm. Terakhir, analisa data mengungkapkan bahwa Lucy membangun persahabatan dengan Mr. Tumnus dan Giant Rumblebuffin, Edmund membangun persahabatan dengan the White Witch dan semua anak – anak Pevensie membangun persahabatn dengan Aslan, keluarga Beaver dan penduduk Narnia lainnya. Hubungan ini dibangun berdasar beberapa alasan yang berdampak pada anak – anak Pevensie dan penduduk Narnia sehingga mereka dapat meningkatkan kepribadian menjadi individu – individu yang lebih baik dan membawa komunitas di Narnia hidup bahagia. Kata Kunci: cinta, cinta filia, persahabatan Abstract It is not easy to define what love is but love has been a general theme used in songs, movies, literature and everyday’s life. Love is a necessary ingredient in individual’s life and it seems impossible to live without love. Love represents not only an erotic thing but also the relationship among friend or it is known as philia love or friendship. Philia love or friendship is also mostly used as a theme in children literature. This study formulates two questions; how philia love is represented by the characters in a popular children literature, C.S Lewis’ Narnia: The Lion, The Witch and The Wardrobe and what the reasons and impacts of employing philia love are in that novel. This study focuses on discussing philia love depicted through the characters (The Pevensie children and Narnia inhabitants) in C.S Lewis’ Narnia: The Lion, The Witch and The Wardrobe and their reasons and impacts of employing philia love. Library research by intensive reading is used as an approach in analyzing data. To answer the first problem, this study uses Fromm’s theory of love, elements of philia love or friendship by Moore and Lewis and supported by Aristotle and several researchers on friendship. The second problem is answered by using Aristotle’s concepts of motives in building friendship supported by Lewis and Fromm. Last of all, the analysis reveals that Lucy makes a friendship with Mr. Tumnus and Giant Rumblebuffin, Edmund makes a friendship with the White Witch, and all The Pevensie children build a friendship with Aslan, the Beavers and other Narnia inhabitants. These interactions are built on several reasons which can make the children and Narnia inhabitants improve their personalities into better individuals and bring the community in Narnia live happily. Keywords: love, philia love, friendship INTRODUCTION The good and evil, love and friendship, heroes and heroine, are mostly the themes of which fantasy fictions deal with. By understanding the meaning of the themes, readers can draw some messages from them. It also encourages children readers to learn about moral values, how to build a good friendship to others, how to love everyone and be a humble person, etc. Fantasy fictions had been written a long time ago in which they were well known as classic fantasy. Classic fantasy fictions were firstly aimed for young readers such as Peter Pan and The Wonderful Wizard of Oz. However, George MacDonald wrote his first fantasy novel for adult readers, The Princess and The Goblin and Phantastes. He was popular with his work and influenced other fantasy writers, such as J.R.R Tolkien and C.S Lewis. Tolkien was also popular with his novels The Hobbit and The Lord of The Rings and Lewis was mostly popular with his series novels The Chronicles of Narnia. His series novels contain seven books: The Lion, the Witch and the Wardrobe (1950), Prince Caspian: The Return to Narnia (1951), The Voyage of the Dawn Treader (1952), The Silver Chair (1953), The Horse and His Boy (1954), The Magician’s Nephew (1955) (the #6 book which was replaced to be the #1 book by Harper Collins Press since the story tells about the history of creating Narnia), and The Last Battle (1956). Accomplished by C.S. Lewis in March, 1950, Narnia: The Lion, The Witch and The Wardrobe had been a popular book. That it has been over sixty years from the date of firstly published, the novel gives many influences to other works. Although it is a children literature, its fantasy world has inspired many authors to create novels – not only for children readers but also for adults – that many of them also become popular, for instance J.K Rowling’s Harry Potter Novel Series. Alike the author of Harry Potter Series above, Philip Pullman used – not only the same theme, but also the same characters like talking animals – in his fantasy series His Dark Materials. The existence of wardrobe and the girl – as it is found in Narnia: The Lion, The Witch and The Wardrobe – also can be found in another Pullman’s, Northern Light. Other authors and their works inspired by Narnia: The Lion, The Witch and The Wardrobe are Neil Gaiman’s young-adult nouvella Coraline; Greg Egan’s science-fiction short story Oracle; and Lev Grossman’s The Magician which is also New York Times best-seller. Interestingly, The Lion, The Witch and The Wardrobe achieved the 25 best children fantasy book at the first position (bestfantasybook.com). According to a 2004 study, almost all school in San Diego, California use the novel as a reference book read by teachers and seventh-grade students. It was also #58 on New York Time’s 2005 list of the 100 best English-language novels published since 1923. Based on a 2007 online poll, the novel was named “Teacher’s Top 100 Books for Children by the National Education Association in the U.S and it was one of the second most common books which read by U.K adults and children after Alice in The Wonderland. In the novel’s firstly time of publish, it had been sold over 100 million copies in 47 languages (http://en.wikipedia.org/wiki/The_Chronicles_of_ Narnia. retrieved on October 12, 2012). Because of Lewis’ great talent in writing, he became the leading figure in English Faculty at Oxford University and being the chairman of Medieval and Renaissance Literature at Magdalene College, Cambridge. Beside that, Lewis accepted many achievements in his writing, such as Optimism which won Chancellors English Essay Prize in 1912, The Allegory of Love which also won Gollancz Memorial Prize for Literature in 1937, The Last Battle (the series #7 of The Chornicles of Narnia) which won Carnegie Medal for best book children in 1956 (http://www.thestonetable.com/landing_pages/1,3.html. Retrieved on October, 12th 2012). The struggle in saving Narnia from the cruel White Witch involves all Pevensie children and Narnia inhabitants. They discuss about plans together, they prepare the strategies to attack the White Witch and they gain their victory together. Their adventure in Narnia depicts how the children have a close relationship with the inhabitant of Narnia such as Mr.Tumnus, The Beaver, Aslan, etc. The Pevensie children love all Narnia inhabitants and the vice versa. Their love reveals a certain love which is, in term, called as Philia love. Philia love means friendship in modern Greek. Aristotle in Book VIII of Nicomachean Ethics (Ross, 2006:81), describes Philia love as a dispassionate virtuous love which includes loyalty to friends, family, and community, and requires virtue, equality and familiarity. It is a virtue or implies virtue, and is beside most necessary with a view of living. In ancient texts, philia denoted a general type of love, used for love between family, between friends, a desire or enjoyment of an activity, as well as between lovers (http://www.religiousforums.com/forum/general-religious-debates/76681-agape-love-vs-philia-love.html). Beside Aristotle, Lewis, who was the writer of the novel discussed in this study, said that philia love or friendship is the most prized which is independent and uncompulsively. It is also the only love which close to God or angels. Besides discussing the relationship between the Pevensie children and the inhabitant of Narnia, the children also depict how their relationship among themselves. The children’s friendship both among themselves and between them and Narnia inhabitants are based on several reasons or motives such as respect, utility and pleasure. These motives can bring them to different impacts. The impact of being respect as the motive is a strong friendship. One of the best examples of it is the friendship between Lucy and Mr. Tumnus. Otherwise, when the motives are pleasure and utility, the friendship will not last longer. The friendship between Edmund and the White Witch is as the example. Nonetheless, based on facts lay on background of the study above, then the problems are formulated and divided into two: (1) how is philia love represented in C.S Lewis’ novel Narnia: The Lion, The Witch and The Wardrobe?and (2) What are reasons and impacts of the employment of philia love among the characters in C.S Lewis’ novel Narnia: The Lion, The Witch and The Wardrobe? As referred to background and statement of the problems above, the purpose of the study are devoted as results of analyzing the problems: (1) To identify the representation of philia love in C.S Lewis’ novel Narnia: The Lion, The Witch and The Wardrobe, and (2) To recognize the reasons of the employment of philia love and its impacts to the characters in C.S Lewis’s novel Narnia: The Lion, The Witch and The Wardrobe. In accordance, this study is expected to help readers to realize that the novel can be used to interpret one of the types of love, philia love or also known as friendship. Besides, the study can also help readers to understand more about the implementation of philia love or friendship. Thus, the readers can also be expected to learn how to build a good friendship. Regarding the novel type as a children literature, moreover, this study may help the readers who concerned with teaching on literature as a reference. Furthermore, the readers of the novel Narnia: The Lion, The Witch and The Wardrobe are also expected to easily understand the content of the novel itself especially about the relationship concerned in building friendship among Pevensie children and the inhabitant of the Narnia. RESEARCH METHOD The main source of the study is from C.S Lewis’ Narnia: The Lion, The Witch and The Wardrobe which is published by Harper Collins Press in 1994. Data are taken from the novel concerning with speeches and thoughts, actions, and attitudes of the characters which are related to the matter of discussion, philia love. It is including quotations, phrases, dialogues and monologues. The method of collecting data which is used in this study is literary research. It does not use statistical method and it is not served in numbering or table. Library research used an approach in analyzing data. The kind of library research is intensive or closely reading to search quotations or phrases and to analyze data. Reading the novel is the first step to do. Then, searching the quality of the novel is done by reading the achievements of the novels as well as the author’s. To decide an interesting topic from this novel is the next step. After drawing an interesting topic, it is important to mind-map the concepts of the topic. Collecting data concerned with the topic in some tables will help to make the mind-map. Mind-mapping the concepts and the data help arranging the thesis. After making the mind-map, the next step is to analyze the data. Theoretical framework will be used for subsequent analyzing. After that, to find the result of the discussion, drawing conclusion is completed after the analysis. The concept applied to discuss the matter in this study is philia love or friendship which is described by C.S Lewis, the author of Narnia:The Lion, The Witch and The Wardrobe, in his book titled The Four Loves. Besides, there are some concepts of love, philia love and its characteristics stated by, Aristotle, Fromm, Moore and other researchers on friendship used in the analysis. LOVE Regardless of economics, race or status, people value love and recognize that love will shape what is good and true. To love means to care, to recognize the essential humanity of the other person, to have an active regard for that person’s development. May (1953:206) defines love as a delight in the presence of the other person and an affirming of value and development as much as one’s own. According to Warga (1983:313), love is an intense feeling of positive regard toward another person in which the needs and desires of that person are put above those of the one who loves. Love is more than an emotion. It includes the attitudes of trust, positive acceptance and approval, helpful and a wish for the good things for the loved one. It also includes some behaviors that are along with the attitude such as affection, joy, sexual desire, anger, respect, sympathy and empathy. Erich Fromm in The Art of Loving (2006:72), who had conducted many studies of thought and love, describes that love has four elements: care, responsibility, respect, and knowledge. They are the set of creative relationship of love. The first element is caring or usually called as a concern. According to Fromm, love is as the active concern for the life and the growth of that which people love. When the active concern is lacking, there is no love. Fromm says in Warga (1983:314), care as loving one/s’ health, growth, stability, and welfare. Care is about to share the feeling of joy and pain. Care also implies to the mutuality that means giving as well as taking. Responsibility, according to Fromm (2006:76), is an entirely voluntary act. It really means responding to the needs, both are expressed or unexpressed, of another human being. To be responsible means to be able to “respond”. Thus love, as Fromm describes it in Warga (1983:314), is a relationship of giving and taking, of mutual interaction. Love involves a sharing and returning. The third element is respect. By respect, Fromm explains that there must be an ability to see a person as he is and to be aware of his unique individuality. Respect means the concern that the other person should grow and unfold as he is. Thus, Respecting, according to Fromm in Warga (1983:314), does not mean to change the personality of the loved one into a certain image, but it is to accept his or her personality in the way he or she is. According to Fromm (2006:78), to respect a person is not possible without knowing; care and responsibility would be blind if they were not guided by knowledge. He adds in Warga (1983:314) people in love must know each other. For real love, people must experience each other and for real knowing one has to know the intimate, real self, free from the mask of polite society. Obviously, there are different kinds of love. According to Warga (1983: 315), love is divided into two, sexual or erotic love and nonsexual love. Nonsexual love is also divided into two types: love of humanity and familial love. Familial love, according to Fromm, is divided into two types, motherly love and brotherly love. Motherly love is regarded for a weak and helpless while brotherly love is the friendly love that exists among equals. A fantasy writer, C.S Lewis, has similar idea about the types of love. According to Lewis in his book The Four Loves (1960), love is divided into four types. They are storge, philia, eros and agape. PHILIA LOVE Philia is the Greek word which means friendship. It also comes from another Greek word “philos,” meaning loving. Today the label “Platonic love” is commonly used to describe true friendship, referring to the ideal of non-sexual connection, deriving from the Greek philosopher Plato’s incorporeal, abstract, perfect world of ideas. According to Nelson’s New Illustrated Bible Dictionary (1995), Philia love means to have ardent affection and feeling—a type of impulsive love. This is the natural, human type of love and affection that people have for a friend and is often defined as "brotherly love." It is also defined in Bible, John ( 21:15-16), Jesus asked Peter if he loved Him with the agape type of love and Peter responded that he had the normal human philia type of love for Him. Philia is also a neighbourly love - the bonds of friendship that bind people together in community. More formally, the word philia is defined as "the reserve” of human warmth, enthusiasm and generosity that nourishes and stimulates the fellowship at the heart of civic life (http://www.philia.ca/cms_en/page1171.cfm). In other words, today’s communities are inherently resilient. The lens of resilience is fundamental to Philia because it makes people re-examine assumptions about how individuals and communities function and grow. It reminds them that they are not merely passive recipients in need of outside support and intervention, but have a built-in capacity to heal, adapt, transform and survive. Phillia, according to Feist (2008:353) is an intimate nonsexual friendship between two people. It cannot be rushed and takes time to grow, to develop, to sink its roots. Rollo May in Feist (2008:353) also states that Philia does not require that we do anything for the beloved except him, be with him, and enjoy him. It is friendship in the simples, most direct terms. Philia, then, can grow as love between siblings or lifelong friends. Boer in Baron’s Social Psychology Second Edition (2005:8) is also explaining about friendship growing between siblings. According to him, the relationship between siblings is different with the relationship between parents and their children. The relationship between siblings often involves a combination of the affection, hate and competition. Floyd adds in Baron’s book that siblings are most possible to feel the closeness between them when they are able to share opinions and memories, experience friendship and help each other to overcome a difficult situation. In the relationship of siblings, one of them may take a role as a “parent” however there are some studies that also find that siblings are most often employing their relationship as a close friendship or merely an acquaintance. Lewis explores the four types of love, which are also described in Bible, in his book The Four of Loves (1960). According to him, Philia is a love among friends-it is a friendship. Philia was appreciated strongly in the ancient world but in this modern life, there are very few truly friendships among people because it is also very few people have experienced it. To Lewis, philia love is friendship which is seemed the happiest and the most fully human of all loves; the crown of life and the school of virtue. It can be traced back to the story of Pylades and Orestes, Roland and Oliver, Amis and Amile as well as the story of David and Jonathan in Bible. Friendship are of practical value to the Community, for example Mathematics effectively began when a few Greek friends got together to talk about numbers, lines and angels. Nevertheless, it may bring benefactor to the community. As a benefactor it helps the community not to live but to live well. However, the danger to the community is real. Friendship can be a school of virtue; it also can be a school of vice. It is ambivalent. It makes good men better and bad men worse. Lewis (1960:76) adds that in a good friendship, each member often feels humility towards the rest. He sees that they are splendid and counts himself lucky to be among them. Aristotle in Ross (1954:85) adds that some men are good in respect of friendship, for those who live together in happiness in each other and get benefits each other. So, people can conclude whether one is good or not through his friends or through his building friendship for a good man in becoming a friend becomes a good to his friends and loves what is good for both and makes an equal return in goodwill and in pleasantness. However, through friendship there will be reformation in the community; there will be the Renaissance, the movement against slavery and other changes within the community. Lewis states (1960:63) what is now the Royal Society was originally a few gentlemen meeting in their spare time to discuss thing which they (and not many others) had fancy for. What people call now “The Romantic Movement” once were Mr. Wordsworth and Mr. Coleridge talking incessantly about a secret vision of their own. Others again would say that friendship is extremely useful, perhaps necessary for survival, to the individual. There is a friend that sticketh closer than a brother. But, it means that the word friend is “ally”. In ordinary usage friend means or should mean, more than that. According to Aristotle in Ross (1954:83) such a friend, which means ally, will find a certain motive to connect each other. The motive may be pleasure or utility. But, when the motive of the friendship is done away, the friendship is disappear. They do not even find each other pleasant; therefore they do not need such a companionship unless they are useful to each other. Friendship would be something like saying, “What? You too?”. In this kind of love, according to Lewis as Emerson said, Do you love me? means Do you see the same truth?. A man who agrees with the asker’s answer, can be his friend. CHARACTERISTICS OF PHILIA LOVE Daniel Hruschka, summarized by an anthropologist, Krystal D’Costa, adds that friendship is a social relationship in which partner provides support according to their abilities in times of need, and in which this behavior is motivated in part by positive affect between partners. A common way of signaling this positive affect is to give gifts on regular basis. Without friends, he adds, people are certaintlu bereft. He identifies some elements of friendship: (1) mutual aid, (2) gift giving, (3) self-disclosure, (4) informality, (5) frequent socializing, (6) positive affect, (7) need, (8) equality, (9) voluntariness, and (10) privateness. By mutual aid, it suggests that individual has each other’s interests at heart and will make sacrifies as needed. The common thread that connects mutual aid is how it is given – willingly and freely. By gift giving, Hruschka describes that it reaffirms social ties and bounds. It represents the giver’s goodwill and is the primary means of identifying exploitative relationships. Self-disclosure is also important in building friendship. It imparts a sense of vulnerability and binds individual together. However, sharing secrets is not required for friendship and may be avoided because it can be leveraged during interfamily disputes. Informality is also the part of the characteristics of friendship. Nicknames, teasing and mocking (and farting) are all things that a friend can do in the company of other friends without fear or reprisal. Informality can lead to frequent socializing in which Baron (2003:9) adds that once there is a close friendship built, it is affected for both parties to spend most of their time together and interact each other in various situation. Beside that informality also can bring a favorable feeling towards friends which is another strong common thread giving positive affect in a friendship. Need, according to Hruschka, is similar to mutual aid. It refers to aid offered as necessary, without balancing mechanism. A friend does not offer aid in a “tit-for-tat exchange.” However, Hruschka also states about equality. In this term, equality is not related with need, it means as a friend he should minimize attributes and style of interaction that make him between or among his friends appear unequal. Therefore, there is no gap in friendship. Levine (2012) adds that in friendship one must take the blinders such as eliminating people who older, younger, richer, poorer, taller, shorter and etc. Potential friends are all around. Aristotles in Ross (1954:86) also states that friendship may come to whoever who stand in inequality. Older to younger may come to friendship for example the friendship between father to son. Another inequality is rulers to subhect such as the friendship between man to wife. Although friendship is conducted among inequals, the love should be proportional. In friendship, there is also voluntariness. One makes some others to be his friends and it is not forced by anyone: parents for example. When a friendship built, it is a freewill of a person without any influences from others. By privatness, Hruschka states that individuals are responsible for maintaining their relationships. Otherwise there may be communities which member may invite commentary from others. Every friendship begins with some signs that two people are interested in becoming friends. The first characteristic of friendship is openness which shows the sign that one likes someone else and wants to be his or her friend. Without being open other people, a person must be difficult in interacting with other especially building a friendship. According to Eileen Kennedy-Moore (2012), a Ph.D specialized in growing friendship, being open to other people can be started by saying greetings which involves the eye contact, warm smile and clear utterance. Saying the other person’s name also make the greeting more personal. Besides saying greeting, giving compliments is another easy way to build friendship. By delivering compliment, the person, which the one wants to be friend with, feel that he or she is appreciated in finer qualities. Surely, the compliments are delivered sincerely by also showing a kindness. Besides giving compliment, a small kindness can be another way to signal liking to build friendship. This could mean lending a pencil to a classmate, saving them a seat, helping them carry something or sharing a lunch treat. Kindness is the best way to begin a friendship. Lewis in The Four Loves (1960) also explains that the kindness is a must to make friendship. He describes how friend relationship can be begun by sharing everything that the two people have, just like said in Bible that the more a person share the Heavenly Bread, the more he or she shall have and the more God gives bless to him or her. (Lewis, 1960:57). Another ingredient in making friendship is similarity. Moore states (2012) that similarity attracts because it is satisfying at both a practical and an emotional level. At a practical level, it is easy to have friend who enjoy the same activities they do. At an emotional level, similarity provides a sense of comfort and validation. If expressing openness unlocks the door of friendship and similarity predicts who is most likely to walk through that door, the third ingredient of friendship is what encourages people to sit down and stay awhile, so friendship can grow. The ingredient is shared fun. According to Moore, to have fun with a peer, a person needs to behave in ways that the other enjoys, communicate about likes and dislikes and avoid or resolve any disagreements. Aristotle in Ross (1954:82) states that friendship is build based on the mutual love. If it is not mutual love then it cannot be called as friendship. Friends will also wish some goodness one another and do something for the sake of his friend. In friendship there must be mutually recognized as bearing goodwill or equal return in goodwill and wishing well to each other. Lewis also adds that every friendship is must be useful for both parties. If it is useful for only one person and not both, it is not friendship. REPRESENTATION OF PHILIA LOVE Based on the analysis, the representation of philia love manifests itself into three forms. There are philia love between the pevensie children and Narnia inhabitants, philia love among the Pevensie children and philia love as alliance. Philia love or C.S Lewis said as Friendship is firstly depicted by Lucy which is firstly pictured as a shy and fearful girl. She finds Narnia through the wardrobe in a space room in Professor’s house and meets a faun there. Although it was the first time she meets a strange creature, she is not scary. She, otherwise, is brave enough to greet the Faun first politely. Lucy’s first meeting with Mr. Tumnus shows that both Mr. Tumnus and Lucy build a strong friendship each other. Their friendship is firstly showed by representing Fromm’s respect or accepting the other in the way he is. Lucy accepts Mr. Tumnus as her friend although he is a faun, half human, half goat. Mr. Tumnus also accepts Lucy as a human being although he has never met a human before. Besides respect, the friendship is build based on Moore’s openness and Lewis’ mutual interaction. They show a nice and polite greeting at the first time meeting and they act in a good manner each other. Beside to Mr. Tumnus, Lucy also makes a friendship with Giant Rumblebuffin. Lucy builds a friendship with Giant Rumblebuffin when she lends her handkerchief to when he needs something to wipe his sweat. Lucy represents Fromm’s respect and responsibility. She accepts the way Giant Rumblebuffin he is, a huge creature. She is also responsible to what the giant needs, a handkerchief, by lending him hers. The giant is also responsible to what Lucy needs by accepting the handkerchief to appreciate her goodness. Both of them represent Lewis’ mutual interaction. Their respect, responsibility and mutual interaction depict Moore’s kindness. Lucy’s kindness is lending the giant her handkerchief and Giant Rumblebuffin’s kindness is by accepting Lucy’s handkerchief and appreciating it although the handkerchief is too small compared with his large face. Beside Lucy, her sibling also makes friendship with other Narnia inhabitants such as The Beaver family and Aslan. The Pevensie children represent Fromm’s respect by accepting and putting trust to Mr. Beaver which is a talking animal. Besides respect, they also represent Moore’s similarity which means that they are in the same goal, against the White Witch. Besides, Mrs. and Mr. Beaver depict Moore’s kindness by helping the children to find Aslan in order to save Mr. Tumnus and their brother, Edmund, who has been in the White Witch’s side. They also give the children dinner and breakfast in the way to find Aslan. The children also return their kindness by helping them preparing dinner and breakfast. Both of them represent Lewis’ mutual interaction by being useful to each. The children also make friendship with Aslan by showing Moore’s openness. Peter greets Aslan respectfully by raising his sword as a symbol of giving an admiration to a king. Aslan welcomes the children and the Beaver family warmly by mentioning their names one by one showing that the relationship is closer. Besides, they also represent similarity. The children, the Beavers and Aslan are in the same side, against the White Witch. The friendship is also built among the Pevensie children. It is represented when Peter saves Susan who is in the danger, about being killed by the White Witch’s wolves. Peter represents Fromm’s caring and responsibility. Peter cares his sister’s welfare by giving her an aid although he is afraid of fighting with wolves. His responsibility is represented by responding Susan’s need, an aid. Besides, Lucy’s saving Edmund in the battle field also represents friendship among the children. Lucy gives a magic cordial to Edmund when he is about to die. Lucy represents Fromm’s caring and responsibility. She also represents Moore’s kindness. Friendship is also described as an ally or alliance in which the parties involving in friendship find a certain motive to connect each other. However, when the motive has done, the friendship may come to the end. This kind of friendship is represented by Edmund and the White Witch. The first time the White Witch meets Edmund, she give a compliment to him, stating that he is a nice boy and deserves to be a king. Besides, she also gives her a drink and some Turkish Delight from her magical bottle which represents a kindness. Compliment and kindness are the characteristics of friendship. However, the person does not acting them willingly. The White Witch delivers compliment and gives Edmund a kindness is based oncertain motive. It is aimed to make Edmund believe that she is a nice person so that he is willing to do what she orders. REASONS AND IMPACTS OF THE EMPLOYMENT OF PHILIA LOVE Fromm has explained that loves has four elements and knowledge is one of them. According to him, knowledge means to know each other and free from the mask of polite society. Before one experiences further relationship with other person, he or she must know who the person is, including the friendship relationship. Therefore, knowledge can be a tool to identify the reason behind a friendship is built. The first evidence showing that the characters use knowledge as their reason to start a friendship is when Lucy makes Mr. Tumnus as her friend and the vice versa. Lucy’s knowledge about Mr. Tumnus is gained by an openness when both of them introduce themselves to each other. Lucy greets Mr. Tumnus well and politely and she introduces her name to him. It indicates that she is a good girl. Mr. Tumnus also gives her a good response by bowing to her indicating that he puts a respect to Lucy. Through a nice introduction like this, Lucy knows that Mr. Tumnus is a good person. Mr. Tumnus also invites her to his house to take a rest and have a conversation about what Narnia is which Lucy is still confused about. Lucy accepts Mr. Tumnus’ invitation and she is not afraid of Mr. Tumnus although it is her first time to see a faun, a half human-half goat creature. It is her knowledge that Mr. Tumnus is a good person that leads her to fulfill the invitation. Beside because of knowledge, Lucy and Mr. Tumnus’ friendship is based on being lovable and trusted each other. It is based on Aristotle’s concept that in friendship there must be two parties behave in those ways. Lucy has been lovable to Mr. Tumnus since she respects him by greeting him politely although he is a strange creature. Mr. Tumnus is also proved that he is a lovable person by answering Lucy’s greeting and he even give her a bow. It also makes Lucy trust him that he is a nice faun she ever meets. Therefore, she is brave enough to accept Mr. Tumnus’ invitation to come to his house and make him as a friend. On the other hand, Mr. Tumnus’ first reason to be friendly to Lucy is because he had a bad intention to her to bring her to White Witch. His job is to catch the Sons of Adam and the Daughter of Eve to be killed by the White Witch. However, Mr. Tumnus cannot do what he has been ordered to do by the White Witch. It is because Lucy has been so lovable to him. Lucy’s reason to make a friendship with Mr. Tumnus is based on respect of which Aristotle describes as being lovable to other. She makes Mr. Tumnus as her friend sincerely. Lucy’ being friendly to Mr. Tumnus makes him change his mind to bring her to the White Witch. This is the impact of a friendship that can make a person better than before. It is like Aristotle’s explanation that a friendship is a school of virtue. It can help the young to keep from error. When Mr. Tumnus is with Lucy, he will not do his bad intention to bring her to the White Witch. He is free from the mistake or error because of bad intention. The second evidence that knowledge is as the reason the friendship is built is represented by the Pevensie children and The Beavers. The children’s knowledge about the similarity between them and Mr. Beaver because he has shown that he is in the same side with Mr. Tumnus. It means that he is a good creature. He proves it by showing the handkerchief of which Lucy gives to Mr. Tumnus. He also tells the children that Mr. Tumnus has been trusted to him to keep and show the handkerchief to the children if he meets them. Through this handkerchief, the children trust that Mr. Beaver is in the good side. According to Lewis, friendship is about when both parties see the same truth. Both the children and Mr. Beaver see the same truth, against the White Witch. The children’s motive to make Mr. Beaver as their friend is also based on the mutual love or respect. Mr. Beaver is lovable and friendly to the children. It is proved by his invitation to the children to come to his house for a dinner because he knows that the children must be hungry and tired walking in the forest. The children are also lovable to him by being politely asking Mr. Beaver if he is a good creature or not. Beside making friend with the Beaver family, the children also have a friendship relationship with Aslan. The first reason they make Aslan as their friend is based on knowledge about similarity. They know that Aslan is in the same side as them because Mr. and Mrs. Beaver tell them about Aslan. Beside that, Aslan also has the same truth as the children, against the White Witch. Both Aslan and the children also represent mutual love or respect as their motive to build friendship. The children behave politely to Aslan and they are lovable to him so that Aslan trust them. Aslan also treats the children well. Moreover, even though he has higher position than the children since he is the King of the Kings, he is able to be equal to them. Both Aslan and the children have a good motive in building friendship. Another friendship is depicted by Lucy and Giant Rumblebuffin. Lucy’s motive to build a friendship with Giant Rumblebuffin is based on Aristotle’s explanation about respect. It is being lovable to each other. Lucy has proved that she is lovable to Giant Rumblebuffin by lending him her handkerchief. Giant Rumblebuffin has also been lovable to Lucy since he makes Lucy’s very useful by using her handkerchief even though its size is too small compared by his large face. According to Aristotle, there are two remained motives of building a friendship relationship. They are the motive of pleasure and utility. Once a person involving in a friendship based on those motives has gotten what they are intended to get pleasure or benefit from others, they may break their friendship. Moreover, if the other parties do not give the pleasure and is not useful anymore to him, he may be hostile to them. It is depicted by the White Witch. Her motive to make Edmund as her friend is based on utility. Lewis describes it as an ally. Edmund is useful for her because through Edmund she wants to meet the other children who will be killed. However, Edmund is failed to bring his brother and sisters. All the things that the White Witch has promised to Edmund is only a lie. She just pretends to be kind so that Edmund believes that she is a good person. She does not build a friendship otherwise it is only an ally. According to Aristotle, the White Witch’s motive is done and their friendship is disappear. Moreover, the White Witch treats Edmund worse than before. On the other hand, Edmund’s motive to make friendship with the White Witch is based on pleasure. Since Edmund has eaten Turkish Delight which comes from the White Witch’s magic wand, he wants to be the White Witch’s friend in order to be able to eat Turkish Delight again. By eating Turkish Delight a lot, Edmund gets a great pleasure. Therefore, he does whatever the White Witch orders him to do although he has understood that the White Witch is cruel. The friendship between the children and the Beaver family, Aslan and Giant Rumblebuffin bring a good impact both for the individual and for the community. For the individual, the impacts can be seen from the Pevensie children. For the community, the impacts can be seen from the Narnia inhabitants. The first impact can be seen from Lucy’s personality growth. At the first scene, it is told that Lucy is a very fearful character. However, after Lucy finds Narnia through the wardrobe, her personality has changed. She is brave enough to greet and introduce herself to Mr. Tumnus who is stranger to her. It is because he also treats Lucy well. It makes them build a strong friendship. Because of their strong friendship, Lucy becomes a brave girl. She is not afraid of exploring Narnia with her siblings in order to save Mr. Tumnus. She is brave enough to meet Aslan, a very big Lion, and makes him as her friend. She is also not afraid of Giant Rumblebuffin otherwise she loves him to be her friend. Because of her bravery, Lucy also gets a dub as Queen Lucy the Valiant (Lewis, 1994:135). Lucy’s being changed of her personality is like Aristotle’s explanation that a friendship can be the school of virtue. It makes a good person becomes better than before. Beside Lucy, Edmund’s personality is also changed. Edmund is known as a rude boy. He does not obey his sister’s command to him. He always fight with Peter and he likes mocking Lucy. In Narnia, he also meets the White Witch which makes him worse because she is a bad character. There is also a bad person makes friendship with another bad one. According to Aristotle, friendship may lead a bad person becomes worse. It is depicted by Edmund. He betrays other Pevensie children who are in the side of Aslan to the White Witch because he wants all the pleasure only for him. However, Edmund realizes that the White Witch is not a good friend at all. He realizes because his siblings have built a good friendship with other Narnia inhabitants who save him from the White Witch unless he is almost killed by her. Moreover, he really hates the White Witch and he does his best in the battle so that he can bring the good Narnia inhabitants to the victory although it makes him seriously injured. Edmund’s changed personality what Aristotle explains that friendship is the school of virtue. Besides giving impacts to an individual, friendship also bring a good impact for a community or a group. The first evidence is the Pevensie Siblings, Peter, Susan, Edmund and Lucy. The Pevensie children have unhealthy relationship before. They often fight one another. However, after they are in Narnia, they learn to build friendship among themselves. Because friendship, according to Hruschka, may bring a positive effect towards the parties involving in that relationship, the Pevensie children get a positive affect from it. It is the growth of the love among siblings. It is one of the virtue that the children can get from making friendship among them. If in the house they all are fighting and mocking one another, in Narnia they help one another. Beside that, they learn how to cooperate with friends and help each other like what they have done with the Beaver family. All the things are successful to make the Pevensie children united and the love among them is stronger than before. Beside for the Pevensie children, the friendship also brings a good impact to Narnia. It is based on Lewis that friendship is of the practical value to the community. It helps the community to live well and bring the community to the reformation. The old Narnia, in which the White Witch sits on her throne, is fulfilled by gloomy condition. The good Narnia inhabitants cannot be free. They always live in fear of being changed into stones by the White Witch. They also live in all-years winter but without Christmas. They do not live happily. However, the children who are the new Kings and Queens of Narnia are successful in governing Narnia. It is because Lucy’s friendship with Mr. Tumnus and the children friendship with the Beaver family, Aslan and other good Narnia inhabitants which can make them to be a good Kings and Queens. The children have made a reformation to Narnia because they share their visions with their friends. They discuss and plan a strategy to defeat the White Witch together and they fight her together. They bring a good impact to Narnia, a new life which is happier than before. All the Narnia inhabitants live happily and peace in Narnia. CONCLUSION There are two important conclusions drawn: the characters reveal philia love or friendship and they represent several reasons and impacts of philia love or friendship. First, this study reveals philia love or friendship which is employed by the Pevensie chidren among themselves and between them and the Narnia inhabitant. Philia love or friendship has some characteristics or elements such as, an openness, compliment, kindness, shared fun, mutual love, caring, respect and responsibility. By those elements, it can be concluded that the Pevensie children are making friendship with the Narnia inhabitants such as Mr. Tumnus, The Beaver family, Aslan, Giant Rumblebuffin and other good Narnia inhabitants. They start the friendship by giving a good introduction such as greeting and mentioning the other’s name. They also give admiration so that the other parties, the Narnia inhabitants, feel appreciated. Some kindness as the best way in building friendship are also given by the Pevensie children therefore it leads to a strong friendship between the children and the good Narnia inhabitant. A mutual interaction is conducted too by the children and the Narnia inhabitants to return the kindness one another. However, there is one of the Pevensie children, Edmund, who makes a wrong friendship with the White Witch. She is a bad character, therefore their friendship is not a real friendship because she has a bad intention to Edmund. This kind of friendship is called alliance which is done on certain motive. Beside, The Pevensie children also make friendship relationship among themselves which is proved by Peter’s aid for Susan and Lucy’s aid for her brother, Edmund. There are three kinds of motive in building friendship. A Friendship between the Pevensie children and the good Narnia inhabitants is based on Aristotle’s first motive, respect. Because friendship is the school of virtue, by employing this motive, both parties can take remarkable advantages. The impacts can be for individuals and for a community. For the individual, it is proved by Lucy who is not a sensitive girl anymore otherwise she is valiant, Mr. Tumnus who cancels his bad intention to Lucy, Edmund who realizes that he is guilty by being the White Witch’s friend. For the community it makes the Pevensie children closer than before and it makes Narnia inhabitants can live in happiness since they are free from the all-years winter caused by the White Witch’s spell. The second motive, utility, and the third one, pleasure, are done by the White Witch and Edmund in their friendship as alliance. Based on utility, the White Witch misused Edmund to do her bad plan, killing Sons of Adam and Daughters of Eve who are Edmund’s siblings. The impact of this motive makes the White Witch break her friendship with Edmund because he cannot be useful for her. Edmund’s motive to make the White Witch his friend is based on pleasure of eating Turkish Delight because he wants eat it more. However, the White Witch cannot give him Turkish Delight since he cannot do her command. Therefore, his love to the White Witch is gone and their friendship is also disappeared. REFERENCES Al Islam, Faris Arshad. 2012. Severus Snape’s Storge Love in J.K Rowling’s Harry Potter Novel Series. Unpublished. Surabaya: State University of Surabaya Baron, Robert A. and Donn Byrne. 2005. Psikologi Sosial. Edisi Kesepuluh. Jilid 2. Translated by Ratna Juwita. Jakarta: Erlangga D’Costa, Krystal. 2012. On My Shelf: Friendship: Development, Ecology and Evolution of a Relationship (Review). From http : // www. anthropologyinpractice.com/2010/10/on-my-shelf-friendship-development.html Retrieved on August, 11th 2013 Enny. 2007. Structuralism of Chronicles of Narnia The Lion The Witch and The Wardrobe by C.S. Lewis. Unpublished. Jakarta: Binus University Fromm, Erich. 2006. The Art of Loving. The World Literature English – Korean Bilingualism. Seoul: Choun Publishing Co. Feist, Jess and Gregory J. Feist. 2008. Theory of Personality Seventh Edition. New York: McGraw – Hill Co Falvlun.2012. Agape Love vs Philia Love. From http://www.religiousforums.com/forum/general-religious-debates/76681-agape-love-vs-philia-love.html. Retrieved on October, 12th 2012 Goodreads.2011.The Lion, The Witch and The Wardrobe. From http : // www. goodreads.com /book/show/100915.The_Lion_the_Witch_and_the_Wardrobe. Retrieved on October 5th 2012 Koesbianto, Sarah Fransisca. 2009. The Ways the Four Pevensie Siblings Help Aslan in C. S Lewis’ The Chronicles of Narnia: the Lion, the Witch and the Wardrobe. Unpublished. Surabaya: Petra Christian University Levine, Irene. S. 2012. Five Simple Ways to Improve Your Friendships in 2012. From http://www.psychologytoday.com/blog/the-friendship-doctor/201201/five-simple-ways-improve-your-friendships-in-2012. Retrieved on August, 11th 2013 Lewis, C.S. 1960. The Four Loves. New York: Harcourt . 1994. Narnia: The Lion, The Wi tch and The Wardrobe. New York: Harper Collins Publishers Inc. Moore, Eileen Kennedy. 2012. How Children Make Friends). From http : // www. psychologytoday. com / blog / growing – friendships / 201209 / how – children – make - friends. Retrieved on August, 11th 2013 Nielsen, Katherine. 2003. The Nature of Love, A Vigil of Two. From http://scoutscan.com. Retrieved on October, 11th 2012 Orobko, Angela Kowitz. 2012. Philia Love. From http://akissofbliss.wordpress.com/2012/02/13/philia-love/. Retrieved on October, 11th 2012 Philia. 2012. Definition of Philia. From http://www.philia.ca/cms_en/page1171.cfm. Retrieved on October, 12th 2012 Ross, W.D. 1954. The Nicomachean Ethics of Aristotle. London: Oxford Univ. Press. The Stone Table. 2008. A Biography of C.S Lewis (1898-1963). From http : // www. thestonetable.com / landing_pages /1,3.html. Retrieved on October 5th 2012 Warga, Richard G. 1983. Personal Awarness: A Psychology of Adjustment. New York: McGraw – Hill Co